Mengembangkan Media Pembelajaran: Analisis Kebutuhan Pada Materi Exterior Light System - Gofani Fajri; Priyono Priyono; Catur Setyawan Kusumohadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This research and development aim to present the results of the analysis of the need for media development for learning in vocational schools on exterior lights system materials. In this research, the needs analysis has referred to: (1) vocational schools are obliged to prepare students with relevant competencies to fill the needs of prospective workers in the world of work or industry; (2) The new world of work demands a higher level of thinking and skills (3) The problem of learning exterior lights system materials that are theoretical; (4) Media required in the practice of exterior lights system. This research uses a series of unstructured observation methods, open question questionnaires, as well as unstructured interviews in gathering information in the field. The result of this study is: (1) Unstructured observation results are the discovery of the problem that 70% of the daily test results of exterior lights system materials of grade XI Electrical Avionic students under the minimum completion criteria (below the grade of 75). (2) The results of the open question questionnaire are the majority of students (96%) students need practice through learning media so that learning outcomes can be improved so as to achieve minimum completion criteria. (3) The results of unstructured interviews to subject teachers are in line with the results of the questionnaire i.e. teachers are still teaching with powerpoint media and lecture methods because there is no learning medium for practical students. The conclusion of this study is that students and teachers need media for practical activities. Therefore, this research and development was conducted to research and develop the media practice material exterior lights system.